Atendimento Educacional Especializado - AEE: Necessidade e funcionamento no município de Apodi/RN - Menezes, Rayssa Rafaela de Lima (2016)
This article is an exploratory research on the Specialized Educational Attendance (SEA), in the city of Apodi / RN. Through documentary analysis and interviews, the investigative work, based on studies and on the legislation that deal with the theme, it was verified how the SEA works in the city, according to the need for this service in schools and an inclusive education. Intended for students with special educational needs this service is offered in room specifies: Multifunctional Resource Room (SRM), they’re found in schools that have a number of students with any disability or other special educational needs. The results show that only two schools offer SEA in the city, in focus, even though a needed service, thus, these schools have become supplemental or complementary support for the development in the learning process of children with learning difficulties. However, it was realized that the services offered by SEA are not always executed with quality, due to some difficulties, such as: lack of determination (by the school staff and the government), parents' resistance to accept that children need a differentiated teaching and learning, no compromise in the frequency of SEA, among others. Therefore, it was noted that, we still 5 need greater knowledge and involvement of managers and teachers of schools in order to become really a service to support the inclusive process of students in regular education.